Value of the systemic immunoinflammatory index, nutritional risk index, and triglyceride-glucose index in predicting the condition and prognosis of patients with hypertriglyceridemia-associated acute pancreatitis - Yuan Zhen Wang; Ya Ling Yun; Ting Ye; Wen Tun Yao; Yu Feng Guo; Li Ya Huang (Frontiers in Nutrition)
ObjectiveThe study aimed to investigate the function and prognosis of pancreatitis in patients with hypertriglyceridemia-associated acute pancreatitis (HTGAP), as assessed by the systemic immunoinflammatory index (SII), nutritional risk index (NRI), and triglyceride-glucose index (TyG).MethodsA total of 300 patients with HTGAP who were admitted to the General Hospital of Ningxia Medical University from January 2022 to June 2023 were selected. These patients were divided into three groups based on the severity of their condition: the mild acute pancreatitis (MAP) group, the moderate-to-severe acute pancreatitis (MSAP) group, and the severe acute pancreatitis (SAP) group. The SII, NRI, and TyG index in the three groups were recorded and compared. The value of these indices in predicting the occurrence of HTGAP was analyzed using a receiver operating characteristic (ROC) curve.ResultsThe SII and TyG index values in the SAP group (3259.4 ± 2795.8, 4.5 ± 1.1) were higher than those in the MSAP group (2563.7 ± 1614.1, 4.3 ± 0.8) and MAP group (1991.1 ± 1566.8, 4.1 ± 0.8), and the difference was statistically significant (p < 0.005). The ROC curve analysis showed that the AUC value of the combined SII, NRI, and TyG index for predicting SAP occurrence was 0.705 (95%CI:0.632 ~ 0.778).ConclusionThe SII, NRI, and TyG index are related to the severity of HTGAP, and a combination of the three can better predict the occurrence of SAP.